1995
DOI: 10.1111/j.1748-0361.1995.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

A Logit Analysis of the Likelihood of Leaving Rural Settings for Registered Nurses

Abstract: This study examined the net effects of individual and community factors on the likelihood of registered nurses leaving current jobs using a logit analysis. Based on data from a survey of 2,509 rural nurses, four separate models were estimated and compared: one for nurses in rural settings as a whole and the other three for nurses in hospitals, skilled nursing facilities, and community/public health agencies. Results of the general model indicated that nurses' marital status, age, position, income, job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 17 publications
3
52
0
2
Order By: Relevance
“…Regarding factors related to nurse turnover, age, job title, nursing experience, community satisfaction 2) , marital status 2,11,12) , living together with a child 11) , moving 12) , salary [11][12][13] , burnout 10,23) , job satisfaction 2,4,13,32) , hardness 4) , interpersonal relationships with doctors, senior nursing staff and patients 12,13) , organization commitment 32) , and lumbar pain 33) have been reported. These factors differed from those affecting the rapid turnover of novice nurses in university hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding factors related to nurse turnover, age, job title, nursing experience, community satisfaction 2) , marital status 2,11,12) , living together with a child 11) , moving 12) , salary [11][12][13] , burnout 10,23) , job satisfaction 2,4,13,32) , hardness 4) , interpersonal relationships with doctors, senior nursing staff and patients 12,13) , organization commitment 32) , and lumbar pain 33) have been reported. These factors differed from those affecting the rapid turnover of novice nurses in university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is hard to expect that enough nurses with the skills needed to meet today's highly advanced medical standards will be educated. While the turnover of nurses with long careers 1) and the factors affecting it have been investigated [2][3][4] , only a few studies on novice nurses have been conducted 5) . It has been reported that novice nurses find it hard to form an accurate perspective of their profession and to obtain job satisfaction [6][7][8] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, job satisfaction among those working as staff nurses in nursing homes was lowest of all work settings. Lower levels of job satisfaction have been linked with increased likelihood of turnover (Pan et al 1995). A recent survey reported annualized turnover rates for nursing home staff RNs and LPNs at 56.2% and 53.6%, respectively (American Health Care Association 2002).…”
Section: Nurse Contractingmentioning
confidence: 99%
“…The issues that apply to rural primary-care clinicians also apply, although in a more local sense, to nurses. Recent studies find significant nonwage influences on the decision by nurses to enter or remain in a rural setting (64,65).…”
Section: Rural Health Professionalsmentioning
confidence: 99%